Viewpoint of Mothers of Premature Newborns about Nursing Supports in Neonatal Intensive Care Units - Elyas Zavalgard; Ehsan KhazemNejad Leili; Masoumeh Jafari Asl; Seyedeh Zahra Shafipour (Journal of Holistic Nursing and Midwifery)
Introduction: Prematurity is the leading cause of mortality in newborns without congenital anomalies worldwide. A premature newborn has a devastating effect on parents'roles, especially the mothers , and creates sentimental and vague feelings for mothers. Although advances in technology and high levels of nursing care provide mothers with adequate support and relative independence in child care, it is practically difficult to terminate nursing care and leave it to the mothers.